Revealing the dust attenuation properties on resolved scales in NGC 628 with SWIFT UVOT data. Issue 1 (19th March 2019) - Decleir, Marjorie; De Looze, Ilse; Boquien, Médéric; Baes, Maarten; Verstocken, Sam; Calzetti, Daniela; Ciesla, Laure; Fritz, Jacopo; Kennicutt, Rob; Nersesian, Angelos; Page, Mathew
ABSTRACT: Understanding how dust attenuation laws vary between and within galaxies is a key question if we want to reliably measure the physical properties of galaxies at both global and local scales. To shed new light on this question, we present a detailed study of the slope and bump strength of the attenuation law in the nearby spiral galaxy NGC 628 at the resolved spatial scale of 325 pc. To do so, we have modelled a broad multiwavelength data set from the ultraviolet (UV) to the infrared (IR) with the state-of-the-art SED fitting code cigale, including SWIFT UVOT data for which we have developed a new optimized reduction pipeline. We find that the median dust attenuation curve of NGC 628 is fairly steep, but not as steep as the SMC curve, and has a sub-MW-type UV bump. We observe intriguing variations within the galaxy, with regions of high A V exhibiting a shallower attenuation curve. We argue that the flattening of the curve is due to a dominance of absorption over scattering events at higher A V . No trend between the bump strength and the IRAC 8.0 $μ$ m emission was found. However, this does not necessarily rule out polycyclic aromatic hydrocarbons as the main contributors to the UV bump.